2019
DOI: 10.3389/fendo.2019.00559
|View full text |Cite
|
Sign up to set email alerts
|

GHRL Gene Leu72Met Polymorphism and Type 2 Diabetes Mellitus: A Meta-Analysis Involving 8,194 Participants

Abstract: Background: Although many studies indicate a positive correlation between GHRL gene Leu72Met polymorphism and an increased susceptibility to type 2 diabetes mellitus (T2DM), inconsistencies between independent studies still remain. Objective: Considering the inconsistencies between them, we have performed the current meta-analysis study. The objective of this study is to better examine the correlation of the GHRL gene Leu72Met pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In humans, the GHRL gene (Gene ID: 51738) is located in 3p25-26 and comprises 7 exons. The five exons code the precursor preproghrelin with 117 amino acids and exons 1 and 2 encode the functional 28 amino-acid region (3,(13)(14)(15). The GHRL gene is highly polymorphic and has non-coding or coding region SNPs (more than 300) (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, the GHRL gene (Gene ID: 51738) is located in 3p25-26 and comprises 7 exons. The five exons code the precursor preproghrelin with 117 amino acids and exons 1 and 2 encode the functional 28 amino-acid region (3,(13)(14)(15). The GHRL gene is highly polymorphic and has non-coding or coding region SNPs (more than 300) (3).…”
Section: Discussionmentioning
confidence: 99%
“…The GHRL gene is highly polymorphic and has non-coding or coding region SNPs (more than 300) (3). Among them, the Leu72Met (+408C>A) polymorphism of the GHRL gene, located on the second exon, replaces the leucine at the 72 nd amino acid with a methionine by switching cytosine to adenine (15). The GHRL Leu72Met polymorphism does not change the sequence of mature ghrelin since it lies outside the region where the mature ghrelin protein is encoded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association analysis with T2D, showed that 72Met allele and Leu72Met genotype were protective against T2D, but after the adjustment, only the 72Met allele remained associated, suggesting that the protective effect of Leu72Met is given by 72Met allele. To this respect, it has been described that the 72Met allele induces protection against T2D in Caucasians [13], whereas the opposite occurs in Asiatic and Danish populations [14,25,27,28]. Moreover, the 72Met allele has also, been associated as a protective against insulin resistance and body fat accumulation [26,29].…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility to T2DM is determined by an interplay of genetic and metabolic factors [ 5 ]. Recently several genes ascertaining the existence of T2DM have garnered attention such as ABCA1 , SOD2, SLC30A8 , KCNJ11, ADIPOQ, TCF7L2 , IL-10 , PON2 , and DPP- IV [ 7 ].…”
Section: Introductionmentioning
confidence: 99%